Cotton for My Shroud - Saxena, Nandan; Bahl, Kavitha (India : Bahl, Kavitha, 2011)
Since 1995, a quarter of a million Indian farmers have committed suicide - the largest wave of recorded suicides in human history. Most were cotton farmers from Vidarbha in Maharashtra. Once known for its fine cotton, it is now called the “graveyard of farmers.” The escalating cost of inputs like seed, fertilizer and pesticide has made farming unsustainable. The lack of resources and institutional credit for sowing the fields in the summer drives poor farmers to end their lives. In the winter, the depressed rates of cotton become the proverbial last straw. Cotton for my Shroud investigates the ongoing farmer suicide crisis in India and the culpability of the multinational Monsanto and the Indian government. It examines the idea of a second colonization of India stemming from corporations’ strategic control of seed supply and the corruption of politicians who are willing to help.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films